Ciguatoxin-Producing Dinoflagellate Gambierdiscus in the Beibu Gulf: First Report of Toxic Gambierdiscus in Chinese Waters - Yixiao Xu; Xilin He; Wai Hin Lee; Leo Lai Chan; Douding Lu; Pengbin Wang; Xiaoping Tao; Huiling Li; Kefu Yu (Toxins, 2021)
Ciguatera poisoning is mainly caused by the consumption of reef fish that have accumulated ciguatoxins (CTXs) produced by the benthic dinoflagellates Gambierdiscus and Fukuyoa. China has a long history of problems with ciguatera, but research on ciguatera causative organisms is very limited, especially in the Beibu Gulf, where coral reefs have been degraded significantly and CTXs in reef fish have exceeded food safety guidelines. Here, five strains of Gambierdiscus spp. were collected from Weizhou Island, a ciguatera hotspot in the Beibu Gulf, and identified by light and scanning electron microscopy and phylogenetic analyses based on large and small subunit rDNA sequences. Strains showed typical morphological characteristics of Gambierdiscus caribaeus, exhibiting a smooth thecal surface, rectangular-shaped 2′, almost symmetric 4″, and a large and broad posterior intercalary plate. They clustered in the phylogenetic tree with G. caribaeus from other locations. Therefore, these five strains belonged to G. caribaeus, a globally distributed Gambierdiscus species. Toxicity was determined through the mouse neuroblastoma assay and ranged from 0 to 5.40 fg CTX3C eq cell−1. The low level of toxicity of G. caribaeus in Weizhou Island, with CTX-contaminated fish above the regulatory level in the previous study, suggests that the long-term presence of low toxicity G. caribaeus might lead to the bioaccumulation of CTXs in fish, which can reach dangerous CTX levels. Alternatively, other highly-toxic, non-sampled strains could be present in these waters. This is the first report on toxic Gambierdiscus from the Beibu Gulf and Chinese waters and will provide a basis for further research determining effective strategies for ciguatera management in the area.